2020
DOI: 10.1097/dss.0000000000002471
|View full text |Cite|
|
Sign up to set email alerts
|

Dermoscopic Findings in the Presurgical Evaluation of Basal Cell Carcinoma. A Prospective Study

Abstract: BACKGROUND Surgery is the best treatment for basal cell carcinoma (BCC); however, incomplete excisions are possible. OBJECTIVE Assessment of the accurateness of dermoscopy and clinical evaluation in the detection of borders of BCC and description of dermoscopic findings in clinically healthy tissue surrounding BCC. MATERIALS AND METHODS Eighty-eight lesions with clinical dermoscopic diagnosis of BCC were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…A recent study compared clinical and dermoscopic margin demarcation and showed that these findings were often missed on clinical assessment. 5 Our study has limitations. Initial margins were not the same for all tumors, and our findings are limited to head tumors referred for MMS, an area typically with more photodamage than the trunk.…”
mentioning
confidence: 89%
“…A recent study compared clinical and dermoscopic margin demarcation and showed that these findings were often missed on clinical assessment. 5 Our study has limitations. Initial margins were not the same for all tumors, and our findings are limited to head tumors referred for MMS, an area typically with more photodamage than the trunk.…”
mentioning
confidence: 89%
“…Moreover, the preoperative dermoscopic assessment using non-classic BCC criteria including pink-white areas and short telangiectasias in the area between clinically and dermoscopically detected margins, helps define the neoplasm's margins and to achieve a really radical excision (fig. 4C) [32].…”
Section: Dermoscopic Assessment Of the Surgical Margins Before Excisionmentioning
confidence: 99%
“…Particularly, basal cell carcinoma (BCC) dermoscopic patterns have been described both for pigmented and nonpigmented lesions, with histopathological correlation and diagnostic accuracy that ranges from 95% to 99%. 7,[13][14][15] During MMS procedure, dermoscopy and VDS can guide the excision by a better definition of neoplastic margins, sometimes identifying specific structures not clinically evident at naked eye. However, preoperative assessment of deep margins is difficult to achieve.…”
Section: Dermoscopy and Videodermoscopymentioning
confidence: 99%